1995
DOI: 10.1002/1097-0142(19950901)76:5<750::aid-cncr2820760507>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the cytologic examination of pure pancreatic juice in the diagnosis of early neoplasia of the pancreas

Abstract: Background. The early diagnosis of pancreatic carcinoma through the use of traditional radiographic or ultrasonographic methods is extremely difficult. Methods. To detect an early and potentially curable cancer of the pancreas, endoscopic retrograde pancreatography (ERP) and aspiration cytology of pure pancreatic juice were performed in 295 consecutive patients who had symptoms or findings that suggested pancreatic disease but in whom there was neither a pancreatic mass nor ductal stenosis. Results. Positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Four papers30, reported in situ adenocarcinoma of the pancreas and intraductal carcinoma of the pancreas with minimal pancreatic parenchymal invasion regardless of tumor size. Mucin‐producing pancreatic cancers with marked dilatation of the main pancreatic duct or multicystic dilatation of the branch pancreatic duct,41 and cystadenocarcinomas42 were excluded from this study.…”
Section: Patientsmentioning
confidence: 99%
“…Four papers30, reported in situ adenocarcinoma of the pancreas and intraductal carcinoma of the pancreas with minimal pancreatic parenchymal invasion regardless of tumor size. Mucin‐producing pancreatic cancers with marked dilatation of the main pancreatic duct or multicystic dilatation of the branch pancreatic duct,41 and cystadenocarcinomas42 were excluded from this study.…”
Section: Patientsmentioning
confidence: 99%
“…To detect pancreatic cancer at an early stage, it is essential to perform examinations of the pancreatic juice from patients who have abnormal pancreatograms shown by endoscopic retrograde pancreatography (ERP), even if no tumor image is shown by ultrasonography (US), endoscopic ultrasonography (EUS), or computed tomography (CT) (4). Pancreatic juice cytology is a reliable method for the diagnosis of pancreatic cancer (5,6), but its diagnostic rates are not always satisfactory (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Retrograde pancreatography by a duodenoscope for the first time offered the opportunity to obtain directly ductal juice and to achieve tissue diagnosis in pancreatic disease in a minimal invasive manner (Endo et al, 1974;Hatfield et al, 1976). A multitude of studies have demonstrated that the joint application of endoscopy and cytotechniques has the capability to contribute to an improved clinical management (Tatsuta et al, 1983;Venu et al, 1990;Ryan, 1991;Nakaizumi et al, 1995;Enayati et al, 1996). However, while being characterised by a near 100% specificity, the sensitivity of pancreatic juice cytology proved to be unsatisfying because of an often low cell count or cell disintegration (Ferrari et al, 1994).…”
mentioning
confidence: 99%